Gender differences in depression across Europe: a systematic review of cross-national studies. (13th November 2019) - Hagen, D; Goldmann, E
Abstract: Background: Across countries and cultures, depressive disorders are more common among females than among males; however, the magnitude of gender differences varies between populations and may be a result of different country-specific social policies and cultural factors. This systematic review seeks to synthesise evidence from nationally representative, cross-national studies across Europe (EU-28 plus Switzerland and Norway) and to describe the impact of country-specific factors on gender differences in depression. Methods: PubMed, Web of Science, PsycInfo, and Embase were searched through March 2019 for peer-reviewed, nationally representative studies that included at least two European countries, used structured assessment for depressive disorders or symptoms, and reported or allowed for the calculation of gender ratios or differences. No restrictions on language or publication date were applied. Risk of bias was assessed using a tool specifically designed for population-based prevalence studies. Results: Twenty-one studies were included in this review, ten of which were based on surveys limited to older populations. Despite the use of different analytical approaches, metrics, scales, and cut-off points, depressive disorders were more common among females than among males in all but a few instances, with substantial variation in the magnitude of gender differences between countries and across studies. There is evidence of smaller gender differences in Northern Europe and greater gender gaps in Southern and Eastern Europe, as well as among older populations. Conclusions: Despite methodological heterogeneity between studies, there is evidence that gender differences in depression vary substantially across Europe. These differences may be associated with welfare state regimes and appear to be less pronounced in younger cohorts. Further cross-national research on gender disparities in depression between age groups, birth cohorts, and ethnic subpopulations is warranted. Key messages: While depressive disorders are more prevalent among females than among males in virtually all of Europe, the magnitude of gender differences varies substantially between countries. There is some evidence that gender differences in depressive disorders are greater in countries with weaker welfare states and lower macro-level gender equality, as well as among older populations.